Implementasi Nilai Fagogoru terhadap Pencegahan Kasus HIV/AIDS di Wilayah Tambang Kabupaten Halmahera Tengah, Provinsi Maluku Utara - Jenar Yamin; Yenny Puspitasari (Pusat Riset dan Inovasi Nasional, 2025)
The number of HIV/AIDS cases in Central Halmahera has shown a significant increase each year since the establishment of the IWIP company. Data from the past three years reveal that in 2022 there were 80 reported cases, and by 2024 the number had risen sharply to 190 cases. This situation highlights the urgent need for comprehensive prevention efforts that go beyond formal health services and integrate local cultural wisdom. One such approach is through the Fagogoru tradition, a cultural value system that has long been practiced by the community. Fagogoru emphasizes the principles of protection, education, and guidance as moral foundations to prevent behavioral deviations that may lead to the spread of HIV/AIDS. This study aims to support the community in accessing HIV/AIDS services, both at district hospitals (RSUD) and primary health care facilities (FKTP). Community engagement activities were carried out through material presentations, interactive discussions, and the use of pre-tests and post-tests to measure knowledge improvement. Problem analysis was conducted using the USG method (Urgency, Seriousness, Growth), while intervention planning was designed using SWOT analysis. The results show that health promotion is an effective first step in increasing community understanding, awareness, and knowledge about HIV/AIDS. Moreover, findings suggest that dissemination efforts should be intensified through social media, accompanied by stronger integration of HIV/AIDS programs within all health services. Thus, combining local cultural wisdom such as Fagogoru with modern health strategies provides a relevant and sustainable approach to reducing the rising trend of HIV/AIDS cases in Central Halmahera.